Variation in corneal curvature and June 30; 6(3):1-8.thickness after wearing corneal andscleral RGP contact lenses for threemonths in patients of keratoconus - Aamer Ejaz Khan Niazi; Sidra Anwar; Shehnaz Fatima; Abdul Hanan Shahid; Muhammad Ali (Medical Journal of South Punjab, 2024)
Objective: To investigate the changes in corneal curvature and thickness in patients of Keratoconus, wearing Rose k2 corneal and XL (scleral lenses) from last three months.Methodology: Interventional study was conducted at The Keratoconus Clinic, Eye 2 Eye Optometrists Lahore. A total of 44 eyes were fitted with rose k2 corneal (15) and rose k2 XL (29) lenses respectively. Curvature and thickness were measured by keratometry and pentacam scan at two time points: first on lens dispensing visit and three month later after some hours of lens wear. Variation in curvature and thickness were measured.Results: The study comprised twenty-three people with keratoconus (44 eyes). They were all young, healthy adults between the ages of 18 and 45. The 23 subjects included 14 males (27 eyes) and nine females (17 eyes). Eight patients (15 eyes) were using Rose K2 corneal design, whereas fifteen patients were using Rose K2 XL(scleral) lenses (29 eyes). The average optical Pachymetry was ±2.7 percent higher (p